2008
DOI: 10.1097/bcr.0b013e31817db9a5
|View full text |Cite
|
Sign up to set email alerts
|

Burns in Children Caused by Hair Straighteners: Epidemiology and Investigation of Heating/Cooling Curves

Abstract: We recently encountered a number of burns in young children caused by hair straighteners and decided to study their epidemiology. We carried out a retrospective audit from 1999 to 2006. We also conducted laboratory testing of the thermal profiles of four brands of hair straighteners. Eighteen children (aged 8 months to 13.5 years, mean 2.1 years) sustained hair straightener burns. Most (13/18) affected the upper limbs and six involved the lower limbs. Three (16.6%) children required surgery. The mean peak temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…15,16 Skin burns can occur in users and, recently, there have been reports that these devices should be considered household hazards because of the risk of accidental skin burns in children. 15,16 Studies have shown that temperatures of 1758C to 2158C for 5 minutes are sufficient to damage most hair; this threshold may be lower if the heat is applied to damp or chemically treated hair 1,[8][9][10]17 (Figs 3 and 4). Proper use of flat irons involves application of the implement to dry hair, and specialized products may be applied to the hair before pressing to help prevent the burning and allow for smoother hair that remains straight longer.…”
mentioning
confidence: 99%
“…15,16 Skin burns can occur in users and, recently, there have been reports that these devices should be considered household hazards because of the risk of accidental skin burns in children. 15,16 Studies have shown that temperatures of 1758C to 2158C for 5 minutes are sufficient to damage most hair; this threshold may be lower if the heat is applied to damp or chemically treated hair 1,[8][9][10]17 (Figs 3 and 4). Proper use of flat irons involves application of the implement to dry hair, and specialized products may be applied to the hair before pressing to help prevent the burning and allow for smoother hair that remains straight longer.…”
mentioning
confidence: 99%
“…Both have different thermodynamic profiles, for example the ceramic versus the metallic The majority in the literature so far are partial thickness burns requiring conservative management. 3,8,10 However, since these burns are regular to children <5 years and to their hands and feet, these are both categories noted in the guidelines set out in the national burn care review requiring referral to a burns unit. 7 Our cases were not all partial thickness and indeed one necessitated admission because of infection with systemic embarrassment.…”
Section: Discussionmentioning
confidence: 98%
“…4 It has been suggested that product packaging should be labelled with warning notices and that various design modifications should be considered such as a safety catch to allow the jaws of the appliance to be locked together when not in use or a heat resistant 'quiver' in which to rest the device 3 or suitable cooling bags. 8 Public heath campaigns have also been suggested in order to target the consumer. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, as the fickle winds of fashion have changed, so too have the patterns of burns involving hair appliances (Duncan, Waterston, Beattie, & Stewart, 2006). In recent years, several authors have reported the increase in incidence of contact burns from hair straightening devices affecting children (Breuning & Papini, 2007;Mehta, Barnes, Edwin, & Pape, 2008;Wilson Jones, Wong, & Potokar, 2008). These studies have reported on the demographics, epidemiology, impact of injury and heating and cooling curves of the internal surfaces of the hair straightening devices.…”
Section: Introductionmentioning
confidence: 96%